Modern art in detail : 75 masterpieces - Hodge, Susie, 1960- (London : Thames & Hudson, 2017)
Great works of art cannot be fully understood in a single encounter. This is perhaps even truer for modern artworks that may not immediately make sense to, or even appeal to, the casual observer. Viewing an artwork-- whether it is a painting, sculpture, installation, video, or photograph-- as a whole is one method of interacting with it, but a deeper understanding can only be gained by analyzing it in detail. "Modern Art in Detail: 75 Masterpieces" spotlights the finer points that even connoisseurs may miss. The book includes all the minutiae that a quick glance will almost certainly fail to reveal, including subtle internal details. Susie Hodge writes intelligently and informatively about relevant external influences on the artist--everything from global political events to groundbreaking movements such as Cubism, Futurism, and Primitivism, and even scientific and mathematical theories. This book examines seventy-five artworks from the late nineteenth century to the modern day. It treats each of its subjects on its own merits, but it also views each as part of a tradition that links it to the past, which sees artists pass a baton down through the ages. Moreover, it charts the shift from the supremacy of artistic technique to the dominance of the idea or concept behind the object created.
Late 19th century -- Early 20th century -- Post World War II -- Late 20th century -- 21st century -- Glossary.
Includes indexes.
Keywords: Art, Modern